Development of a Computerized Adaptive Testing for Internet Addiction - Zhang, Yong; Wang, Daxun; Gao, Xuliang; Cai, Yan; Tu, Dongbo (Frontiers in Psychology, 2019)
Internet addiction disorder is one of the most popular forms of addition in psychological and behavioral areas and measuring internet addiction becomes increasingly important in practice. This study aims to develop a computerized adaptive testing to efficiently measure and assess Internet addiction (CAT-IA). The four standardized scales were used to build the original item bank. Fifty-nine polytomously-scored items were finally chosen after excluding forty-two items due to failure to psychometric evaluation. Then, for the final 59-item bank of CAT-IA, two simulation studies were conducted to investigate the psychometric properties, efficiency, reliability, concurrent validity and predictive validity of CAT-IA under different stopping rules. The results showed that (1) the final 59 items met IRT assumptions, had high discrimination, good item-model fit and without DIF, and (2) the CAT-IA not only had high measurement accuracy in psychometric properties, but also sufficient efficiency, reliability and concurrent validity and predictive validity. We finally discussed the impact and limitations of CAT-IA and provided several suggestions for future research.